Design and Implementation of a Solar-Powered Automatic Plant Irrigation System in Kampung Gisi, Bintan Regency, Riau Islands - Bonardo, Doli; Alajuri, M. Hasbi Sidqi; Bavitra, Bavitra; Harahap, Basyaruddin Ismail; Afriadi, Arie (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
Agricultural sustainability is essential for rural communities, particularly in Kampung Gisi, where celery cultivation is a major source of household income. However, farmers continue to rely on manual irrigation, which is labor intensive, time consuming, and often inefficient in terms of water use. This study aimed to design and implement a solar powered automatic irrigation system that improves water efficiency while reducing farmers’ workload. The approach addressed these challenges by developing an autonomous system powered by solar energy and guided by soil moisture sensing to optimize water delivery. The proposed system integrates a solar panel, an ESP32 microcontroller, a soil moisture sensor, a relay module, and a DC pump to enable irrigation decisions based on real time soil moisture data. Implementation and testing were conducted in Kampung Gisi, Bintan Regency, Riau Islands. Data collection included site visits and semi structured interviews with local farmers to document existing irrigation practices and constraints. Field trials indicated that the system effectively automated irrigation, and the results showed an approximately 30% reduction in water use compared with manual watering. Prior to deployment, farmers typically spent several hours per day irrigating, whereas the automated system substantially reduced time requirements, allowing farmers to allocate effort to other farm activities. Farmers also reported more stable soil moisture conditions, which supported healthier crop development and improved yields. Overall, the findings demonstrate that the system can enhance irrigation efficiency, reduce labor demands, and support more sustainable agricultural practices. Community participation was critical, as farmers developed technical familiarity and a sense of ownership, which supports long term system viability. These results underscore the role of appropriate technology in strengthening farming communities, and they suggest that future work should prioritize accessibility and scalability to support broader adoption.